Social and charitable impacts of a charity-affiliated sport event: A mixed methods study. Issue 2 (April 2018) - Inoue, Yuhei; Heffernan, Caroline; Yamaguchi, Taku; Filo, Kevin
Highlights: Social and charitable impacts of a charity-affiliated sport event were examined. Interviews and surveys were conducted with host community residents. Social impacts refer to promoting social capital, collective pride, and health. Charitable impacts entail empathy for cause and informational and tangible support. Empathy for cause had the strongest association with social impacts. Abstract: In this mixed methods research, the authors examine a unique type of small-scale event – a charity-affiliated sport event – and define and measure its social and charitable impacts as perceived by residents. Findings from interviews ( N = 37) and surveys ( N = 459) with residents indicated that the event's social impacts can be defined by its capacity to develop social capital, enhance collective identity and pride, and promote sport, health, and well-being. Three types of charitable impacts also emerged, including empathy for cause, informational support, and tangible support. Of them, empathy for cause, which addresses a central social issue in the host community, had the strongest association with residents' perceptions of social impacts. These results provide evidence of a variety of positive impacts that a charity-affiliated sport event has on a community, which can be used to bolster appeals for corporate sponsorship and government support to assist in event delivery.